The Practice and Theory of School Improvement
XII, 312 p.
Keywords: ANDY HARGREAVES Department of Teacher Education, Curriculum and Instruction Lynch School of Education, Boston College, MA, U.S.A. ANN LIEBERMAN Carnegie Foundation for the Advancement of Teaching, Stanford, CA, U.S.A. MICHAEL FULLAN Ontario Institute for Studies in Education, University of Toronto, Canada DAVID HOPKINS Department for Education and Skills, London, U.K. This set of four volumes on Educational Change brings together evidence and insights on educational change issues from leading writers and researchers in the field from across the world. Many of these writers, whose chapters have been specially written for these books, have been investigating, helping initiate and implementing educational change, for most or all of their lengthy careers. Others are working on the cutting edge of theory and practice in educational change, taking the field in new or even more challenging directions. And some are more skeptical about the literature of educational change and the assumptions on which it rests. They help us to approach projects of understanding or initiating educational change more deeply, reflectively and realistically. Educational change and reform have rarely had so much prominence within public policy, in so many different places. Educational change is ubiquitous. It figures large in Presidential and Prime Ministerial speeches. It is at or near the top of many National policy agendas. Everywhere, educational change is not only a policy priority but also major public news. Yet action to bring about educational change usually exceeds people's understanding of how to do so effectively.